Resin particles and manufacturing method thereof
By synthesizing resin particles through a process involving hydrolysis, ring-opening polymerization, and radical polymerization of silane monomers, the challenges of achieving high heat resistance and deformation resilience are addressed, resulting in enhanced performance for resin particles in various applications.
Patent Information
- Application Number
- JP2020082535
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-05-08
- Publication Date
- 2025-05-01
- Estimated Expiration
- 2040-05-08
AI Technical Summary
Resin particles used in various applications, such as liquid crystal display devices, require higher heat resistance and resilience after compression deformation to withstand heat treatment processes and maintain performance.
The method involves synthesizing cyclic polysiloxane compounds through hydrolysis and condensation of silane monomers with polymerizable unsaturated groups, followed by ring-opening polymerization to form chain polysiloxane compounds, which are then radically polymerized to produce resin particles with enhanced heat resistance and deformation recovery.
The resulting resin particles exhibit excellent heat resistance and resilience after compression deformation, ensuring their performance and durability in demanding applications.
Smart Images

Figure 0007671127000001 
Figure 0007671127000002 
Figure 0007671127000003
Abstract
Description
[Technical field]
[0001] The present invention relates to resin particles having excellent heat resistance and restorability after compression deformation, and a method for producing the same. [Background technology]
[0002] 2. Description of the Related Art In recent years, resin particles have been used for a variety of applications, such as spacers for liquid crystal display devices, conductive particles for anisotropic conductive films, fillers for liquid chromatography, lubricants for films, and toners for developing electrostatic images.
[0003] For example, Patent Document 1 discloses organic-inorganic composite particles obtained by hydrolysis / condensation and radical polymerization of a polyfunctional silane compound having a polymerizable unsaturated group, the organic-inorganic composite particles being obtained by carrying out the hydrolysis / condensation and / or radical polymerization in the presence of a surfactant. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2000-204119 A Summary of the Invention [Problem to be solved by the invention]
[0005] Since heat treatment is performed in the manufacturing process of liquid crystal display devices and the like, the higher the heat resistance of the resin particles used as the material, the more preferable it is. In addition, resin particles with even higher heat resistance are required for other applications. Furthermore, depending on the application, recovery after compression deformation is also required.
[0006] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide resin particles excellent in heat resistance and recovery property after compressive deformation, and a method for producing the same. [Means for solving the problem]
[0007] The resin particles of the present invention which have been able to achieve the above object and the method for producing the same are as follows. [1] A step of synthesizing a cyclic polysiloxane compound having a polymerizable unsaturated group by hydrolyzing and condensing a silane monomer having a polymerizable unsaturated group; ring-opening polymerization of the cyclic polysiloxane compound to synthesize a linear polysiloxane compound having a polymerizable unsaturated group; and a step of radically polymerizing the linear polysiloxane compound having a polymerizable unsaturated group. [2] The method for producing resin particles according to [1], wherein the ring-opening polymerization is carried out in the presence of an organic onium compound, an alkali metal hydroxide, or an organic sulfonic acid. [3] The method for producing resin particles according to [1] or [2], wherein the molecular weight of the cyclic polysiloxane compound is 300 or more and 2,000 or less in terms of weight average molecular weight in terms of polystyrene measured by gel permeation chromatography (GPC). [4] The method for producing resin particles according to any one of [1] to [3], wherein the molecular weight of the chain polysiloxane compound having a polymerizable unsaturated group is 1,000 or more and 3,000 or less in terms of weight average molecular weight in terms of polystyrene measured by gel permeation chromatography (GPC). [5] The method for producing resin particles according to any one of [1] to [4], wherein the silane monomer having a polymerizable unsaturated group is a compound represented by the following formula (1):
[0008] [ka] [In formula (1), R x represents a group represented by the following formula (2): R a1 , R a3 each independently represents an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, or an acyl group having 2 to 10 carbon atoms, R a2 represents hydrogen, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 10 carbon atoms,
[0009] [ka] In formula (2), R a4 represents hydrogen, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 10 carbon atoms, R a5 represents an alkylene group having 1 to 10 carbon atoms, m is 0 or 1; n is 0 or 1, * indicates a bond to Si.] [6] Resin particles containing a chain polysiloxane compound having a structural unit represented by the following formula (3):
[0010] [ka] [Equation (3) is —Si(R x )(R y )O― units are bonded in succession. o represents an integer of 3 or more; o R x each independently represents an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, or a group represented by the following formula (4), and at least one R x is a group represented by the following formula (4). o R y each independently represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms. * indicates a bond.
[0011] [ka] In formula (4), R b1 represents hydrogen, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 10 carbon atoms, R b2represents an alkylene group having 1 to 10 carbon atoms, m is 0 or 1; n is 0 or 1, * indicates a bond, ** indicates a bond to Si.] [7]R x The resin particles according to [6], wherein the content of is 45% by mass or more and 85% by mass or less. [8] Resin particles according to [6] or [7], having a coefficient of variation of particle size based on number of particles of 10% or less. [9] Resin particles according to any one of [6] to [8], which have a breaking strength, which is the load value at the breaking point of the resin particles in a compression test compressed at a load rate of 2.23 mN / sec, of 15.00 mN or more.
[10] Resin particles according to any one of [6] to [9], wherein the compressive deformation recovery rate of the resin particles is 35% or more and 70% or less, as measured by deforming the resin particles between a maximum load of 9.81 mN and a minimum load of 0.10 mN at a load application rate of 1.49 mN / sec.
[11] The resin particles according to any one of [6] to
[10] , which have a thermal decomposition temperature of 240° C. or higher. Effect of the Invention
[0012] According to the present invention, it is possible to provide resin particles having excellent heat resistance and recovery property after compressive deformation, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The method for producing resin particles of the present invention comprises the steps of: synthesizing a cyclic polysiloxane compound having a polymerizable unsaturated group by hydrolysis and condensation of a silane monomer having a polymerizable unsaturated group; synthesizing a chain-like polysiloxane compound having a polymerizable unsaturated group by ring-opening polymerization of the cyclic polysiloxane compound; and radically polymerizing the chain-like polysiloxane compound having a polymerizable unsaturated group.Thereby, it is possible to provide resin particles having excellent heat resistance and restorability after compression deformation.Each step will be described in detail below.
[0014] [Synthesis process of cyclic polysiloxane compounds] In the process of synthesizing a cyclic polysiloxane compound having a polymerizable unsaturated group by hydrolyzing and condensing a silane monomer having a polymerizable unsaturated group (hereinafter, sometimes referred to as a silane monomer containing a polymerizable unsaturated group), the silane monomer containing a polymerizable unsaturated group may be hydrolyzed and condensed in a solvent containing water. The hydrolysis and condensation may be carried out in the presence of a surfactant. The hydrolysis and condensation may be carried out in any manner, such as all at once, in portions, or continuously. In carrying out the hydrolysis and condensation, a catalyst such as ammonia, urea, ethanolamine, tetramethylammonium hydroxide, an alkali metal hydroxide such as sodium hydroxide, or an alkaline earth metal hydroxide may be used.
[0015] The polymerizable unsaturated group-containing silane monomer is preferably a compound represented by the following formula (1) (hereinafter, may be referred to as polymerizable unsaturated group-containing silane monomer (1)).
[0016] [ka] [In formula (1), R x represents a group represented by the following formula (2): R a1 , R a3 each independently represents an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, or an acyl group having 2 to 10 carbon atoms, R a2 represents hydrogen, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 10 carbon atoms,
[0017] [ka] In formula (2), R a4 represents hydrogen, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 10 carbon atoms, R a5represents an alkylene group having 1 to 10 carbon atoms, m is 0 or 1; n is 0 or 1, * indicates a bond to Si.]
[0018] R a1 ~R a3 Examples of the alkyl group having 1 to 10 carbon atoms in the formula include linear alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, and decyl; and branched alkyl groups such as isopropyl, isobutyl, isopentyl, neopentyl, and 2-ethylhexyl. Of these, linear alkyl groups are preferred. The fewer the carbon atoms in the alkyl group, the faster the hydrolysis rate, so that the alkyl group is preferably 1 to 7, more preferably 1 to 4, even more preferably 1 to 2, and even more preferably 1.
[0019] R a1 ~R a3 In the above, examples of the aryl group having 6 to 10 carbon atoms include a phenyl group, an o-tolyl group, an m-tolyl group, a p-tolyl group, a 2-ethylphenyl group, a 3-ethylphenyl group, a 4-ethylphenyl group, a 2,3-dimethylphenyl group, a 2,4-dimethylphenyl group, an o-isopropylphenyl group, an m-isopropylphenyl group, a p-isopropylphenyl group, a 4-butylphenyl group, etc. The number of carbon atoms in the aryl group is preferably 6 to 9, more preferably 6 to 8, even more preferably 6 to 7, and even more preferably 6.
[0020] R a1 , R a3 In the above formula, examples of the acyl group having 2 to 10 carbon atoms include an acetoxy group, a propionyl group, etc. The number of carbon atoms in the acyl group is preferably 2 to 7, more preferably 2 to 4, even more preferably 2 or 3, and even more preferably 2.
[0021] R a1 ~R a3 may be the same or different groups, but R a1 and R a3are preferably the same group, and R a1 ~R a3 It is more preferable that these are the same group.
[0022] In the polymerizable unsaturated group-containing silane monomer (1), -OR a1 , -OR a3 In the polymerizable unsaturated group-containing silane monomer (1), -OR a1 , -OR a3 is hydrolyzed by water and then condensed to form a cyclic polysiloxane skeleton.
[0023] R x is a group represented by formula (2) and has a polymerizable unsaturated group. Examples of the polymerizable unsaturated group include a vinyl group and a (meth)acryloyl group.
[0024] R a4 is hydrogen, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 10 carbon atoms. a4 is preferably hydrogen or an alkyl group having 1 to 10 carbon atoms, more preferably hydrogen or an alkyl group having 1 to 5 carbon atoms, even more preferably hydrogen or an alkyl group having 1 to 2 carbon atoms, even more preferably hydrogen or an alkyl group having 1 carbon atom, and particularly preferably an alkyl group having 1 carbon atom. As the alkyl group or aryl group, R a1 ~R a3 Examples of the alkyl group and aryl group include the same groups as those mentioned above.
[0025] R a5is an alkylene group having 1 to 10 carbon atoms, and examples of the alkylene group include linear alkylene groups such as methylene, ethylene, propylene, butylene, pentylene, hexylene, heptylene, octylene, nonylene, and decylene; and branched alkylene groups such as methylmethylene, dimethylmethylene, methylethylene, dimethylethylene, methylpropylene, and dimethylpropylene. Of these, linear alkylene groups are preferred. The number of carbon atoms in the alkyl group is preferably 1 to 7, more preferably 1 to 6, even more preferably 2 to 4, and even more preferably 3.
[0026] m is 0 or 1, and preferably m is 1. n is 0 or 1, and preferably 1. The sum of m and n is preferably 1 or 2, and more preferably 2.
[0027] R x The number of carbon atoms is preferably 2 to 10, more preferably 3 to 9, further preferably 5 to 8, and particularly preferably 7.
[0028] R x Specific preferred examples of the alkyl group include a vinyl group; a (meth)acryloyloxy group; and an alkyl (meth)acrylate group such as a methyl (meth)acrylate group, an ethyl (meth)acrylate group, an n-butyl (meth)acrylate group, an isobutyl (meth)acrylate group, or a t-butyl (meth)acrylate group.
[0029] Specific examples of the polymerizable unsaturated group-containing silane monomer (1) include dialkoxysilanes having a (meth)acryloxyalkyl group such as γ-methacryloxypropylmethyldimethoxysilane, γ-methacryloxypropylethyldimethoxysilane, γ-methacryloxypropylmethyldiethoxysilane, γ-methacryloxypropylethyldiethoxysilane, γ-acryloxypropylmethyldimethoxysilane, γ-acryloxypropylethyldimethoxysilane, γ-acryloxypropylmethyldiethoxysilane, γ-acryloxypropylethyldiethoxysilane, γ-methacryloxypropylmethyldiacetoxysilane, γ-methacryloxypropylethyldiacetoxysilane, γ-methacryloxyethoxypropylmethyldimethoxysilane, and γ-methacryloxyethoxypropylmethyldimethoxysilane; and dialkoxysilanes having a vinyl group such as vinylmethyldimethoxysilane and vinylmethyldiethoxysilane. Among these, dialkoxysilanes having a (meth)acryloxyalkyl group are preferred, dialkoxysilanes having a methacryloxy group are more preferred, γ-methacryloxypropylmethyldimethoxysilane, γ-methacryloxypropylethyldimethoxysilane, γ-methacryloxypropylmethyldiethoxysilane, γ-methacryloxypropylethyldiethoxysilane are even more preferred, and γ-methacryloxypropylmethyldimethoxysilane is the most preferred. These may be used alone or in combination of two or more, but are preferably used alone.
[0030] In the synthesis process of the cyclic polysiloxane compound, a silane monomer other than the polymerizable unsaturated group-containing silane monomer may be added. The other silane monomer may be a silane monomer that does not have a polymerizable unsaturated group, and specifically, R x is hydrogen, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 10 carbon atoms. Examples of the alkyl group having 1 to 10 carbon atoms and the aryl group having 6 to 10 carbon atoms include R a1 ~R a3Examples of the other silane monomers include the same alkyl and aryl groups as those listed in 1. Specific examples of the other silane monomers include dimethyldimethoxysilane, diethyldimethoxysilane, dimethyldiethoxysilane, diethyldiethoxysilane, dimethyldiacetoxysilane, diethyldiacetoxysilane, etc. These may be used alone or in combination of two or more.
[0031] The amount of the polymerizable unsaturated group-containing silane-based monomer (1) charged is preferably 50 to 100 parts by mass, more preferably 60 to 100 parts by mass, even more preferably 70 to 100 parts by mass, even more preferably 80 to 100 parts by mass, particularly preferably 90 to 100 parts by mass, and most preferably 100 parts by mass, per 100 parts by mass of the silane-based monomer charged.
[0032] As described above, in the step of synthesizing a cyclic polysiloxane compound, a polymerizable unsaturated group-containing silane monomer may be hydrolyzed and condensed in a solvent containing water, and the hydrolysis and condensation may be carried out in the presence of a surfactant.
[0033] The surfactant can increase the dispersibility of particles in hydrolysis and condensation. Therefore, even if a polymerizable unsaturated group-containing silane-based monomer is used as a raw material, the adhesion between particles is prevented, and particles with a narrow particle size distribution and no aggregation are easily obtained. As the surfactant, any of nonionic surfactants, cationic surfactants, and anionic surfactants may be used, but nonionic surfactants and / or anionic surfactants are preferred in terms of increasing the dispersibility of particles. The amount of the surfactant to be charged is preferably 0.01 to 50 parts by mass, more preferably 0.1 to 30 parts by mass, and most preferably 1 to 20 parts by mass, relative to 100 parts by mass of the polymerizable unsaturated group-containing silane-based monomer. The surfactant may be added in the hydrolysis and condensation and in the subsequent steps, but if the surfactant is added in the hydrolysis and condensation and is present in the subsequent steps, it is not necessary to add it again.
[0034] The solvent may contain an organic solvent in addition to water and a catalyst. Examples of the organic solvent include alcohols such as methanol, ethanol, isopropanol, n-butanol, isobutanol, sec-butanol, t-butanol, pentanol, ethylene glycol, propylene glycol, and 1,4-butanediol; ketones such as acetone and methyl ethyl ketone; esters such as ethyl acetate; (cyclo)paraffins such as isooctane and cyclohexane; ethers such as dioxane and diethyl ether; and aromatic hydrocarbons such as benzene and toluene. These may be used alone or in combination of two or more.
[0035] The hydrolysis and condensation can be carried out, for example, by adding a polymerizable unsaturated group-containing silane monomer to a solvent containing water, and stirring for preferably 10 minutes to 100 hours, more preferably 30 minutes to 50 hours, even more preferably 1 to 10 hours, and even more preferably 1 to 2 hours. The temperature during the stirring is preferably 0 to 100°C, more preferably 10 to 70°C, and even more preferably 20 to 50°C. Alternatively, the particles obtained by such a method may be charged in advance as seed particles in a synthesis system, and the seed particles may be grown by adding raw materials. By these conditions, the average particle size of the resin particles can be controlled to a preferred range described later.
[0036] In the solvent containing water, the water concentration is preferably 50 to 90% by mass, more preferably 60 to 80% by mass. The catalyst concentration is preferably 0.005 to 10% by mass, further preferably 0.01 to 5% by mass. The organic solvent concentration is preferably 1 to 90% by mass, more preferably 5 to 40% by mass. The concentration of the polymerizable unsaturated group-containing silane monomer is preferably 0.1 to 30% by mass, more preferably 1 to 10% by mass. When seed particles are used, the concentration of the seed particles is 0.05 to 15% by mass, more preferably 0.5 to 5% by mass. By setting these concentrations within the above ranges, respectively, it becomes easier to control the coefficient of variation of the particle size to a preferred range described later.
[0037] By hydrolyzing and condensing a silane monomer containing a polymerizable unsaturated group in a solvent containing water under these conditions, particles can be precipitated and a slurry can be generated. The precipitated particles are the product of the hydrolysis and condensation of the silane monomer containing a polymerizable unsaturated group.
[0038] Under the above conditions, a cyclic polysiloxane compound can be synthesized.
[0039] The molecular weight of the cyclic polysiloxane compound is preferably 300 or more and 2000 or less in terms of polystyrene equivalent weight average molecular weight measured by gel permeation chromatography (GPC). This allows efficient ring-opening polymerization. The weight average molecular weight is more preferably 350 or more, even more preferably 400 or more, even more preferably 500 or more, more preferably 1500 or less, even more preferably 1000 or less, and even more preferably 800 or less.
[0040] [Ring-opening polymerization process] In the process of synthesizing a linear polysiloxane compound having a polymerizable unsaturated group by ring-opening polymerization of a cyclic polysiloxane compound, it is preferable to carry out ring-opening polymerization in the presence of an organic onium compound, an alkali metal hydroxide, or an organic sulfonic acid. These reaction catalysts may be used alone or in combination of two or more. At least one selected from the group consisting of an organic onium compound and an alkali metal hydroxide is more preferable, and an organic onium compound is even more preferable. This makes it easier for the cyclic polysiloxane compound to undergo ring-opening polymerization.
[0041] The organic onium compound is an onium compound having at least one hydrocarbon group. The organic onium compound is preferably an organic ammonium compound or an organic phosphonium compound. Of these, an organic ammonium compound is more preferred. The organic ammonium compound is preferably a halogenated quaternary ammonium salt having a hydrocarbon group. The organic phosphonium compound is preferably a halogenated quaternary phosphonium salt having a hydrocarbon group. These may be used alone or in combination of two or more.
[0042] Examples of halogenated quaternary ammonium salts having a hydrocarbon group include tetra-C ammonium salts such as tetraethylammonium chloride, tetraethylammonium bromide, tetrapropylammonium chloride, tetrapropylammonium bromide, tetrabutylammonium chloride, tetrabutylammonium bromide, trioctylmethylammonium chloride, trioctylmethylammonium bromide, octyltrimethylammonium chloride, and octyltrimethylammonium bromide. 1-20 Alkyl ammonium halides; benzyltrimethylammonium chloride, benzyltrimethylammonium bromide, benzyldodecyldimethylammonium chloride, benzyldodecyldimethylammonium bromide, etc. 7-20 Arakirtri C 1-20 Preferred examples of the alkyl ammonium halide include alkyl ammonium halides. 7-20 Arakirtri C 1-20 More preferred are alkyl ammonium halides, more preferred are benzyl trimethyl ammonium chloride, benzyl trimethyl ammonium bromide, benzyl dodecyl dimethyl ammonium chloride, and benzyl dodecyl dimethyl ammonium bromide, and even more preferred are benzyl dodecyl dimethyl ammonium chloride and benzyl dodecyl dimethyl ammonium bromide. These may be used alone or in combination of two or more.
[0043] Examples of halogenated quaternary phosphonium salts having a hydrocarbon group include tetra-C phosphonium salts such as tetrabutylphosphonium fluoride, tetrabutylphosphonium chloride, tetrabutylphosphonium bromide, tetraoctylphosphonium fluoride, tetraoctylphosphonium chloride, and tetraoctylphosphonium bromide. 1-20 Alkylphosphonium halides; tetraphenylphosphonium fluoride, tetraphenylphosphonium chloride, tetraphenylphosphonium bromide, and other tetra-C 6-20Aryl phosphonium halides; benzyltriphenylphosphonium fluoride, benzyltriphenylphosphonium chloride, benzyltriphenylphosphonium bromide, etc. 7-20 Arakirtri C 6-20 Aryl phosphonium halides, etc. These may be used alone or in combination of two or more.
[0044] Examples of the alkali metal hydroxide include lithium hydroxide, sodium hydroxide, potassium hydroxide, etc. Among these, sodium hydroxide and potassium hydroxide are preferred, and sodium hydroxide is more preferred. These may be used alone or in combination of two or more.
[0045] Examples of organic sulfonic acids include alkylbenzene sulfonic acids, such as hexylbenzene sulfonic acid, octylbenzene sulfonic acid, decylbenzene sulfonic acid, dodecylbenzene sulfonic acid, tetradecylbenzene sulfonic acid, and hexadecylbenzene sulfonic acid. 4-20 Among these, alkylbenzene sulfonic acids such as decylbenzene sulfonic acid and dodecylbenzene sulfonic acid are 8-20 Alkylbenzenesulfonic acid is preferred, and dodecylbenzenesulfonic acid is more preferred. These may be used alone or in combination of two or more.
[0046] The temperature during ring-opening polymerization is preferably 0 to 100° C., more preferably 10 to 80° C., and even more preferably 25 to 70° C. The temperature during ring-opening polymerization is preferably the same as that during hydrolysis and condensation. The retention time during ring-opening polymerization is preferably 1 to 8 hours, more preferably 2 to 7 hours, and even more preferably 2 to 6 hours.
[0047] The amount of the reaction catalyst is preferably 1 to 10 parts by mass, more preferably 2 to 7 parts by mass, based on 100 parts by mass of the polymerizable unsaturated group-containing silane monomer. The reaction catalyst is preferably added to the solvent after the synthesis of the cyclic polysiloxane compound. Also, at least a part of the reaction catalyst may be added to the solvent before the synthesis of the cyclic polysiloxane compound, and in this case, a new reaction catalyst may be added to the solvent after the synthesis of the cyclic polysiloxane compound.
[0048] The molecular weight of the linear polysiloxane compound having a polymerizable unsaturated group is preferably 1000 or more and 3000 or less in terms of polystyrene equivalent weight average molecular weight measured by gel permeation chromatography (GPC). By carrying out ring-opening polymerization to bring the molecular weight of the polysiloxane into this range, the recovery rate after compression of the particles, the breaking strength of the particles, and the thermal decomposition temperature of the particles can be improved. The weight average molecular weight is more preferably 1100 or more, even more preferably 1200 or more, even more preferably 1400 or more, more preferably 2500 or less, even more preferably 2200 or less, and even more preferably 2000 or less. The molecular weight is larger than the molecular weight before ring-opening polymerization, i.e., the molecular weight of the cyclic polysiloxane compound.
[0049] [Radical polymerization process] The method of radically polymerizing a chain polysiloxane compound having a polymerizable unsaturated group includes a method of adding a radical polymerization initiator to a solvent containing water of the particles obtained by ring-opening polymerization, dissolving the particles, and polymerizing the particles as they are; a method of isolating the particles obtained by ring-opening polymerization by filtration, centrifugation, vacuum concentration, etc., and then dispersing the particles in a solution containing a radical polymerization initiator, such as water or an organic solvent, and polymerizing the particles. Among these, a method of adding a radical polymerization initiator to a solvent containing water of the particles obtained by ring-opening polymerization, dissolving the particles, and polymerizing the particles as they are is preferable. In addition, a monomer having a radical polymerizable group and a radically polymerizable group may be added during radical polymerization.
[0050] The radical polymerization initiator is preferably a thermal polymerization initiator, and examples thereof include peroxide-based polymerization initiators and azo compound-based polymerization initiators. Examples of the peroxide-based polymerization initiator include benzoyl peroxide, lauroyl peroxide, octanoyl peroxide, orthochlorobenzoyl peroxide, orthomethoxybenzoyl peroxide, methyl ethyl ketone peroxide, diisopropyl peroxydicarbonate, cumene hydroperoxide, cyclohexanone peroxide, t-butyl hydroperoxide, and diisopropylbenzene hydroperoxide. Examples of the azo compound polymerization initiator include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,3-dimethylbutyronitrile), 2,2'-azobis-(2-methylbutyronitrile), 2,2'-azobis(2,3,3-trimethylbutyronitrile), 2,2'-azobis(2-isopropylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-4-methoxy-2,4-dimethylvaleronitrile), 2-(carbamoylazo)isobutyronitrile, 4,4'-azobis(4-cyanovaleric acid), and dimethyl-2,2'-azobisisobutyrate. These may be used alone or in combination of two or more. Among these, organic peroxides are preferred. The amount of the radical polymerization initiator is not particularly limited, but if a large amount is used, the amount of heat generated increases, making it difficult to control the reaction, while if a small amount is used, radical polymerization may not proceed. Therefore, the amount of the radical polymerization initiator to be charged is preferably 0.1 to 5 parts by mass, more preferably 0.2 to 3 parts by mass, relative to 100 parts by mass of the charged amount of the polymerizable unsaturated group-containing silane monomer.
[0051] The temperature during radical polymerization can be appropriately selected depending on the radical polymerization initiator used, but is preferably 30 to 100°C, more preferably 50 to 80°C, from the viewpoint of ease of reaction control. The temperature is preferably higher than the temperature during ring-opening polymerization. The reaction time of the radical polymerization is preferably 1 to 4 hours, more preferably 1 to 3 hours.
[0052] The resin particles produced by radical polymerization may be isolated from the slurry using a conventional method such as filtration, centrifugation, and vacuum concentration. The resin particles are then classified as necessary, usually dried, and optionally calcined. The drying temperature is not particularly limited, but is preferably 50°C to 250°C, more preferably 80°C to 120°C. The drying time is preferably 1 to 3 hours. Ion-exchanged water, methanol, etc. may be used for washing.
[0053] The resin particles thus produced contain a chain polysiloxane compound that includes a structural unit represented by the following formula (3).
[0054] [Resin particles] The present invention also includes resin particles containing a chain polysiloxane compound (hereinafter, sometimes simply referred to as a chain polysiloxane compound) that includes a structural unit represented by the following formula (3). This structure can improve heat resistance and recovery after compression deformation.
[0055] [ka] [Equation (3) is —Si(R x )(R y )O― units are bonded in succession. o represents an integer of 3 or more; o R x each independently represents an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, or a group represented by the following formula (4), and at least one R x is a group represented by the following formula (4). o R y each independently represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 10 carbon atoms. * indicates a bond.
[0056] [ka] In formula (4), R b1 represents hydrogen, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 10 carbon atoms, R b2 represents an alkyl group having 1 to 10 carbon atoms, m is 0 or 1; n is 0 or 1, * indicates a bond, ** indicates a bond to Si.]
[0057] R y As the above, R in formula (1) a2 The same groups as those shown in the above can be used. y may be the same group or different groups, but multiple R y are preferably the same group.
[0058] R x The alkyl group having 1 to 10 carbon atoms and the aryl group having 6 to 10 carbon atoms are R a1 ~R a3 The alkyl group having 1 to 10 carbon atoms and the aryl group having 6 to 10 carbon atoms are the same as those in the above. x may be the same group or different groups, but multiple R x It is preferable that R are the same group. x is more preferably a group represented by formula (4).
[0059] R b1 As the above, R in formula (2) a4 The same groups as those shown in R b2 As the above, R in formula (1) a5 Examples include the same groups as those shown below. m is 0 or 1, and preferably m is 1. n is 0 or 1, and preferably 1. The sum of m and n is preferably 1 or 2, and more preferably 2.
[0060] In the above formula (3), o represents an integer of 3 or more, and is preferably 3 to 21, more preferably 6 to 18, even more preferably 6 to 15, particularly preferably 6 to 12, and most preferably 9. In addition, o is preferably a multiple of 3.
[0061] In the linear polysiloxane compound, it is preferable that the structural units represented by formula (3) that are bonded consecutively in a number of o units are the same structural units. That is, R x are the same, and R y In synthesizing such a chain polysiloxane compound, it is not necessary to use a variety of raw materials, and therefore the quality of the obtained chain polysiloxane compound is stable.
[0062] In 100% by mass of the linear polysiloxane compound, the content of the structural unit represented by formula (3) is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more. On the other hand, the upper limit may be 100% by mass or less, 99% by mass or less, or 98% by mass or less.
[0063] In 100% by mass of the linear polysiloxane compound, the content of the structural unit represented by formula (3) having the group represented by formula (4) is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more. On the other hand, the upper limit may be 100% by mass or less, 99% by mass or less, or 98% by mass or less.
[0064] In the linear polysiloxane compound, preferably 3 to 21 constitutional units represented by formula (3) having a group represented by formula (4) are consecutively bonded. The number of consecutive bonds is more preferably 6 to 18, further preferably 6 to 15, particularly preferably 6 to 12, and most preferably 9.
[0065] The bond * of the portion derived from the polymerizable unsaturated group in the group represented by formula (4) may be bonded to an adjacent group other than the group represented by formula (4), but is preferably bonded to the adjacent group represented by formula (4).
[0066] A linear polysiloxane compound containing a structural unit represented by formula (3) has both ends that are not bonded to each other and is linear. That is, the polysiloxane skeleton in the linear polysiloxane compound does not form a cyclic structure. The groups bonded to both ends of the linear polysiloxane compound are each independently hydrogen, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, an acyl group having 2 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms. Examples of these groups include the above-mentioned R a1 , R a3 Examples of the groups include the same groups as those listed in the above.
[0067] The molecular weight of the chain polysiloxane compound is preferably 1000 or more and 3000 or less in terms of polystyrene equivalent weight average molecular weight measured by gel permeation chromatography (GPC). This can reduce the variation in particle size while improving the heat resistance, breaking strength, and restorability after compression deformation of the resin particles. The weight average molecular weight is more preferably 1100 or more and 2500 or less, even more preferably 1200 or more and 2200 or less, and even more preferably 1400 or more and 2000 or less.
[0068] Resin particle R x The content of R is preferably 45% by mass or more and 85% by mass or less. x By making the content of R 45% by mass or more, the breaking strength of the resin particles can be increased. It is more preferably 50% by mass or more, and even more preferably 60% by mass or more. x By making the content 85% by mass or less, the restorability of the particles during compression deformation can be improved, more preferably 80% by mass or less, and further preferably 70% by mass or less.
[0069] The compressive elastic modulus (10% K value) when the diameter of the resin particle is displaced by 10% is 2500N / mm 2 More than 5000N / mm 2 It is preferable that the 10% K value is 2500N / mm 2 By setting the value to 3000 N / mm or more, the connection reliability of the conductive fine particles obtained by using the resin particles as a base material is improved in low-pressure connection. 2 More preferably, 3500N / mm 2 On the other hand, the 10% K value is 5000N / mm 2 By setting the 10% K value at 4500 N / mm or less, it is possible to easily secure the connection area with the electrode even in a low-voltage connection. 2 Less than 4000N / mm 2 The following is the result.
[0070] The 10% K value is the compressive modulus when a load is applied toward the center of a test particle and the compressive displacement is 10% of the particle diameter. The compressive modulus can be determined by measuring the load value at 10% compressive displacement. More specifically, the 10% K value (compressive modulus at 10% compressive displacement) is determined by measuring the compressive load value using the method shown in the Examples below, and then using the following formula:
[0071]
number
[0072] In the above formula, E is the compressive elastic modulus (N / mm 2 ), F is the compression load (N), S is the compression displacement (mm), and R is the radius of the particle (mm).
[0073] The compressive elastic modulus (20% K value) when the diameter of the resin particle is displaced by 20% is 2200N / mm 2 More than 4000N / mm 2 The 20% K value is preferably 2200N / mm 2By setting the 20% K value at or above, the connection reliability of the conductive fine particles obtained by using the resin particles as a base material is improved. Therefore, the 20% K value is more preferably 2300 N / mm 2 On the other hand, the 20% K value is 4000N / mm 2 By setting the 20% K value to 3000 N / mm or less, it is possible to easily ensure the contact area between the conductive fine particles and the electrode. 2 Less than 2600N / mm 2 The following is the result.
[0074] The ratio of the 10% K value of the resin particles to the 20% K value (10% K value / 20% K value) is preferably 1.1 to 1.7, and more preferably 1.3 to 1.6.
[0075] The number-based average particle diameter of the resin particles is preferably 1.0 to 8.0 μm. If conductive microparticles are produced using resin particles having a number-based average particle diameter in this range, the obtained conductive microparticles are easily used for electrical connection of fine and narrow electrodes and wiring. The number-based average particle diameter of the resin particles is more preferably 2.0 μm or more, even more preferably 3.0 μm or more, even more preferably 4.0 μm or more, particularly preferably 4.2 μm or more, and more preferably 7.0 μm or less, even more preferably 6.0 μm or less, and even more preferably 5.0 μm or less.
[0076] The coefficient of variation of the particle size based on the number of resin particles is preferably 10% or less. If the coefficient of variation of the particle size based on the number of dispersed particle sizes (CV value) is small, it becomes easier to obtain particles with uniform particle size and suppressed aggregation. Therefore, the coefficient of variation of the particle size is more preferably 9% or less, and even more preferably 8% or less.
[0077] The coefficient of variation of the particle size can be calculated based on the following formula. Coefficient of variation of particle size (%) = 100 x (standard deviation of particle size / number-average particle size)
[0078] The number-average particle size and the standard deviation of particle sizes can be calculated from the following formulas by measuring the particle sizes of 100 random particles in an electron microscope image.
[0079]
number
[0080] The breaking strength, which is the load value at the breaking point of the resin particles in a compression test in which the resin particles are compressed at a load loading rate of 2.23 mN / sec, is preferably 15.00 mN or more. When the breaking strength is 15.00 mN or more, when the conductive fine particles containing the resin particles are used in a liquid crystal display device or the like, even if the conductive fine particles are pressurized at a high pressure during the manufacturing process or use process, the conductivity is unlikely to decrease. Therefore, the breaking strength is more preferably 17.00 mN or more, and even more preferably 18.00 mN or more. On the other hand, the upper limit of the breaking strength is not particularly limited, but may be 60.00 mN or less, 50.00 mN or less, 40.00 mN or less, or 30.00 mN or less. The breaking strength can be measured by the method described in the Examples below.
[0081] The compressive deformation recovery rate of the resin particles measured by deforming between a maximum load of 9.81 mN and a minimum load of 0.10 mN at a load loading rate of 1.49 mN / sec is preferably 35% or more and 70% or less. If the compressive deformation recovery rate is 35% or more, the resin particles have excellent indentation properties, so that the conductive fine particles obtained using the resin particles are easy to use for electrical connection. The compressive deformation recovery rate is more preferably 40% or more, even more preferably 45% or more, and even more preferably 50% or more. On the other hand, the upper limit of the resin particles is not particularly limited, but from the viewpoint of preventing damage to the electrode, it is preferably 70% or less, more preferably 60% or less. The compressive deformation recovery rate can be measured by the method described in the examples below.
[0082] The thermal decomposition temperature of the resin particles is preferably 240° C. or higher. When the conductive fine particles containing the resin particles are used in a liquid crystal display device or the like, the conductive fine particles are unlikely to deform even if the conductive fine particles are exposed to high temperatures during the manufacturing process or use process. Therefore, the thermal decomposition temperature is more preferably 250° C. or higher, even more preferably 260° C. or higher, even more preferably 270° C. or higher, and particularly preferably 275° C. or higher. On the other hand, the upper limit of the thermal decomposition temperature is not particularly limited, but may be 400° C. or lower, or may be 300° C. or lower. The thermal decomposition temperature can be measured by the method described in the Examples below.
[0083] The resin particles, in the form of non-conductive or conductive particles, can be used as a conductive material for liquid crystal display elements, spacers for liquid crystal display elements, fillers for liquid chromatography, lubricants for films, toners for developing electrostatic images, etc.
[0084] The resin particles are preferably base particles for conductive particles. Resin particles have excellent heat resistance and recovery after compression deformation, so that conductive fine particles obtained using the resin particles as a base material also have excellent heat resistance and recovery after compression deformation. Examples of the method for making the resin particles into conductive particles include a method of plating the resin particles on the substrate surface by electroless plating, electrolytic plating, etc.; a method of forming a conductive metal layer on the substrate surface by physical deposition methods such as vacuum deposition, ion plating, and ion sputtering; and the like. Among these, the electroless plating method is particularly preferred in that it does not require a large-scale device and can easily form a conductive metal layer. The metal constituting the conductive metal layer is not particularly limited, and examples thereof include metals and metal compounds such as gold, silver, copper, platinum, iron, lead, aluminum, chromium, palladium, nickel, rhodium, ruthenium, antimony, bismuth, germanium, tin, cobalt, indium, nickel-phosphorus, and nickel-boron, and alloys thereof. Among these, gold, nickel, palladium, and silver are preferred because they have excellent conductivity. In addition, nickel, nickel alloys (Ni-Au, Ni-Pd, Ni-Pd-Au, Ni-Ag), etc. are preferable because they are inexpensive. The conductive metal layer may be a single layer or a multi-layer, and in the case of a multi-layer, preferable combinations include, for example, nickel-gold, nickel-palladium, nickel-palladium-gold, nickel-silver, etc.
[0085] The thickness of the conductive metal layer in the conductive particles is preferably 0.01 μm or more, more preferably 0.03 μm or more, even more preferably 0.05 μm or more, and is preferably 0.20 μm or less, more preferably 0.18 μm or less, even more preferably 0.15 μm or less. If the thickness of the conductive metal layer is within the above range, stable electrical connection can be easily maintained when the conductive fine particles are used as an anisotropic conductive material.
[0086] The number-average particle diameter of the conductive particles is preferably 2.0 μm or more, more preferably 3.0 μm or more, and even more preferably 4.0 μm or more, and is preferably 7.0 μm or less, more preferably 6.0 μm or less, and even more preferably 5.0 μm or less. If the number-average particle diameter is within this range, it can be suitably used for electrical connection of miniaturized and narrowed electrodes and wiring.
[0087] The conductive particles can be suitably used as a constituent material of an anisotropic conductive material. By providing the anisotropic conductive material between opposing substrates or between electrode terminals, electrical connection can be achieved. Examples of anisotropic conductive materials include conductive materials for liquid crystal display elements.
[0088] Examples of anisotropic conductive materials include various forms such as anisotropic conductive films, anisotropic conductive pastes, anisotropic conductive adhesives, and anisotropic conductive inks. Anisotropic conductive materials can be produced by dispersing conductive fine particles in an insulating binder resin and forming the material into a desired form. Examples of binder resins include thermoplastic resins such as acrylic resins, ethylene-vinyl acetate resins, and styrene-butadiene block copolymers; curable resin compositions that are cured by reaction with a curing agent such as a monomer or oligomer having a glycidyl group and an isocyanate; and curable resin compositions that are cured by light or heat.
[0089] In the anisotropic conductive material, the content of the conductive fine particles is preferably 1% by volume or more, more preferably 2% by volume or more, and even more preferably 5% by volume or more, and is preferably 50% by volume or less, more preferably 30% by volume or less, and even more preferably 20% by volume or less, based on the total amount of the anisotropic conductive material. This makes it easier to exert the properties of the anisotropic conductive material while obtaining sufficient electrical conductivity. EXAMPLES
[0090] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples, and can be modified as long as it satisfies the spirit of the invention, and all such modifications are included in the technical scope of the present invention. In the following, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass".
[0091] <Physical property measurement method> Various physical properties were measured by the following methods. <Measurement of polymer weight average molecular weight (Mw)> 0.1 g of the particles was dissolved in 1.2 g of tetrahydrofuran (THF), and the weight average molecular weight (Mw) of the polymer was measured using gel permeation chromatography (GPC) under the following conditions. The measurement was performed using the particles after hydrolysis and condensation and before ring-opening polymerization in Production Example 1, the particles after hydrolysis and condensation, ring-opening polymerization and before radical polymerization in Production Example 1, and the particles after hydrolysis and condensation and before radical polymerization in Production Example 2. The weight average molecular weights (Mw) were 528, 1634, and 538, respectively. Equipment: Tosoh Corporation HLC-8420GPC EcoSEC Elite-WS Detector: RI Column: Tosoh Corporation TSKgel ALPHA-M Column temperature: 40℃ Flow rate: 1.0mL / min Calibration curve: Tosoh Corporation TSKstandard POLYSTYRENE (peak top molecular weight (Mp) 5,480,000, 2,890,000, 190,000, 37,900, 5,970, 1,110)
[0092] <Number average particle size of resin particles, coefficient of variation (CV value)> The number-average particle size and the standard deviation of particle size were calculated from the following formula by measuring the particle sizes of 100 random particles in an image taken with a field emission scanning electron microscope (FE-SEM, Hitachi "S-4800"):
[0093]
number
[0094] Furthermore, the coefficient of variation (CV value) of the particle size was calculated based on the following formula. Coefficient of variation of particles (%) = 100 x (standard deviation of particle size / number-average particle size)
[0095] <Number average particle size of conductive fine particles, film thickness of conductive metal layer> Using a flow type particle image analyzer (Sysmex Corporation's "FPIA (registered trademark)-3000"), the number average particle diameter X (μm) of 3000 base particles (resin particles) and the number average particle diameter Y (μm) of 3000 conductive fine particles were measured. The measurements were performed after adding 17.5 parts of a 1.4% aqueous solution of polyoxyethylene oleyl ether (Kao Corporation's "Emulgen (registered trademark) 430"), which is an emulsifier, to 0.25 parts of the particles and dispersing the mixture by ultrasonic waves for 10 minutes. The film thickness of the conductive metal layer was calculated according to the following formula. Conductive metal layer thickness (μm)=(YX) / 2
[0096] <10% K value and 20% K value of resin particles> Using a micro-compression tester (Shimadzu Corporation "MCT-W500"), at room temperature (25°C), a resin particle was spread on a sample stage (material: SKS plate) and a circular flat indenter (material: diamond) with a diameter of 50 μm was used to apply a load to the center of the resin particle at a constant load rate (2.23 mN / sec) up to the maximum load (49.0 mN) in the "soft surface detection" mode, and the load value (10% compression load value) (mN) when the compression displacement became 10% of the number-average particle diameter of the resin particle and the displacement amount (μm) at that time were measured. In the case of 20%, the corresponding load value (mN) and the displacement amount (μm) at that time were also measured. The measurement was performed on 10 different resin particles for each sample, and the average value was used as the measured value. The obtained compression load value (mN) was converted to compression load (N), the obtained displacement (μm) was converted to compression displacement (mm), and the radius (mm) of the resin particles was calculated from the number average particle diameter (μm) of the resin particles, and the following formula was used to calculate the radius (mm): The above measurements were performed in a constant temperature atmosphere of 25°C.
[0097]
number
[0098] <Recovery rate of resin particles> Using a microcompression tester (Shimadzu Corporation "MCT-W500"), at room temperature (25°C), one resin particle scattered on a sample table (material: SKS plate) was compressed toward the center of the particle at a constant loading speed (1.49 mN / sec) to a maximum load (9.81 mN) using a circular flat indenter (material: diamond) with a diameter of 50 μm in the "soft surface detection" mode, and the displacement (μm) at that time was measured and defined as the maximum displacement L1. Next, the load was reduced to the minimum load (0.10 mN) at a constant unloading speed (1.49 mN / sec), and the displacement (μm) between the maximum load and the minimum load was measured and defined as the recovery displacement L2. The recovery rate was calculated from the maximum displacement L1 and the recovery displacement L2 based on the following formula. The measurement was performed on 10 different particles for each sample, and the average value was defined as the measured value. The above measurement was performed in a constant temperature atmosphere of 25°C. Recovery rate (%)=(L2 / L1)×100
[0099] <Resin particle breaking strength and compression deformation rate> When the above particle compression test was carried out, a point was observed where the amount of displacement changed significantly at a certain load value. The load value at this point was taken as the breaking load (mN), and the amount of displacement at this point was taken as the compressive fracture displacement (μm). Using these values, the compressive fracture deformation rate (%) was calculated using the following formula. Compressive fracture deformation rate (%) = (compressive fracture displacement (μm) / particle size before compression (μm)) × 100
[0100] <Thermal decomposition temperature of resin particles> The thermal decomposition onset temperature of the resin particles was measured using a thermogravimetric and differential thermal analyzer (STA7200RV, Hitachi High-Tech Science Co., Ltd.). Specifically, the measurement was performed under the conditions of a sample weight of 20 mg, a heating rate of 10°C / min (maximum temperature reached: 500°C), and nitrogen (flow rate: 200 mL / min). The temperature at which the time change in the weight loss rate (ΔTg / min) exceeded 0.3% / min was defined as the thermal decomposition onset temperature.
[0101] <Initial resistance value> The initial resistance between the electrodes of the obtained connection structure was measured, and an initial resistance of 2Ω or less was evaluated as "○○", a resistance greater than 2Ω but less than 5Ω was evaluated as "○", and a resistance greater than 5Ω was evaluated as "×".
[0102] <Connection reliability> The initial resistance A between the electrodes of the connection structure was measured, and the resulting connection structure was then left in an atmosphere of 85°C and 85% RH for 500 hours, after which the resistance B was measured in the same manner as the initial resistance A. A resistance increase rate (%) calculated based on the following formula of 2% or less was evaluated as "○", and a rate exceeding 2% was evaluated as "×". Resistance increase rate (%) = [(BA) / A] x 100
[0103] <Preparation of resin particles> (Production Example 1) In a four-neck flask equipped with a cooling tube, a thermometer, and a dropping port, 974 parts of ion-exchanged water, 1.96 parts of polyvinyl alcohol (Mitsubishi Chemical Corporation, "GOHSENOL GH-17R"), and 2.04 parts of 28% aqueous ammonia solution were charged and kept at 25°C. 100 parts of silane monomer 3-methacryloxypropylmethyldimethoxysilane (Shin-Etsu Chemical Co., Ltd., "KBM502") and 235 parts of methanol were dropped into the flask, and the internal temperature was kept at 30°C and stirred for 90 minutes to carry out hydrolysis and condensation reaction of 3-methacryloxypropylmethyldimethoxysilane, producing an emulsion of polysiloxane particles having methacryloxy groups (polymerizable polysiloxane particles). The molecular weight of the polymer in the obtained polysiloxane particles was measured using gel permeation chromatography (GPC), and the weight average molecular weight was 528. Molecular weight measurement was performed using a mass spectrometer (JEOL Corporation, "JEOL JMS-T100LP AccuTOF LC-Plus (JEOL MS-5414DART ion source)"), and a cyclic siloxane, which is a trimer of 3-methacryloxypropylmethyldimethoxysilane, was detected ([M+H] 559).
[0104] Next, 5.2 parts of benzyldodecyldimethylammonium bromide (Tokyo Chemical Industry Co., Ltd.) was added as a ring-opening polymerization agent to the reaction solution, and the mixture was maintained at 30° C. for 5 hours to carry out anionic ring-opening polymerization. The molecular weight of the polymer in the resulting polysiloxane particles was measured using gel permeation chromatography (GPC), and the weight average molecular weight was found to be 1634, confirming the increase in molecular weight due to ring-opening polymerization.
[0105] Next, 2.0 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) (manufactured by Wako Pure Chemical Industries, Ltd., "V-65") was added as a radical polymerization initiator to the reaction solution, which was then heated to 65°C under a nitrogen atmosphere and maintained at 65°C for 2 hours to carry out radical polymerization. After cooling the reaction solution, the resulting emulsion was subjected to solid-liquid separation, and the resulting cake was washed with ion-exchanged water and then with methanol, and then dried at 120°C for 2 hours under a nitrogen atmosphere to obtain resin particles (1).
[0106] (Production Example 2) Resin particles were obtained in the same manner as in Production Example 1, except that ring-opening polymerization was not performed. That is, hydrolysis and condensation were performed in the same manner as in Production Example 1, and then radical polymerization was performed in the same manner as in Production Example 1 without ring-opening polymerization, to obtain particles named resin particles (2). The molecular weight of the polymer in the polysiloxane particles obtained by hydrolysis and condensation was measured by GPC, and the weight average molecular weight was 538.
[0107] Table 1 shows the number average particle size, coefficient of variation (CV value), 10% K value, 20% K value, breaking strength, compressive fracture deformation rate, recovery rate, and thermal decomposition temperature of these resin particles (1) and (2).
[0108] <Preparation of conductive particles (formation of conductive metal layer)> Example 1 The resin particles (1) synthesized in Production Example 1 were etched with sodium hydroxide, and then sensitized by contacting with a tin dichloride solution, and then activated by immersing in a palladium dichloride solution (sensitizing-activation method) to form palladium nuclei. Next, 2 parts of the resin particles with palladium nuclei formed were added to 400 parts of ion-exchanged water, and after ultrasonic dispersion treatment, the resulting resin particle suspension was heated in a warm bath at 70°C. In this heated state, 600 parts of an electroless plating solution ("Shumar S680" manufactured by Nippon Kangen Co., Ltd.) separately heated to 70°C was added to cause an electroless nickel plating reaction. After confirming that the generation of hydrogen gas had ended, solid-liquid separation was performed, and the particles were washed with ion-exchanged water and methanol in this order, and vacuum dried at 100°C for 2 hours to obtain nickel-plated particles. The nickel-plated particles were then added to a displacement gold plating solution containing potassium gold cyanide to further plate the nickel layer surface with gold, yielding conductive fine particles (1). The thickness and particle size of the conductive metal layer in the resulting conductive fine particles (1) were as shown in Table 1.
[0109] Comparative Example 1 Conductive fine particles were prepared in the same manner as in Example 1, except that the resin particles (2) synthesized in Production Example 2 were used as the base material.
[0110] <Preparation of connection structure> Anisotropic conductive materials (anisotropic conductive films) were prepared by the following method using the conductive fine particles (1) and (2) obtained in Example 1 and Comparative Example 1. That is, 100 parts of epoxy resin ("JER828" manufactured by Mitsubishi Chemical) as a binder resin, 2 parts of a curing agent ("San-Aid (registered trademark) SI-150" manufactured by Sanshin Chemical Industry Co., Ltd.), and 100 parts of toluene were added to 1 part of the conductive fine particles, and 50 parts of zirconia beads having a diameter of 1 mm were added, and the mixture was stirred and dispersed at 300 rpm for 10 minutes using two stainless steel stirring blades. The obtained paste-like composition was then applied to a PET film that had been subjected to a peeling treatment using a bar coater and dried to obtain an anisotropic conductive film. Furthermore, the obtained anisotropic conductive film was sandwiched between a full-surface aluminum-deposited glass substrate having a line for resistance measurement and a polyimide film substrate having a copper pattern formed at a pitch of 20 μm, and thermocompression-bonded under pressure bonding conditions of 1 MPa and 190° C. to obtain a connection structure. The initial resistance of the resulting connection structure was measured, and a connection reliability test was also carried out. The results are shown in Table 1.
[0111] [Table 1]
Claims
1. A step of synthesizing a cyclic polysiloxane compound having a polymerizable unsaturated group by hydrolyzing and condensing a silane monomer having a polymerizable unsaturated group; ring-opening polymerization of the cyclic polysiloxane compound to synthesize a linear polysiloxane compound having a polymerizable unsaturated group; and a step of radically polymerizing the linear polysiloxane compound having a polymerizable unsaturated group.
2. The method for producing resin particles according to claim 1, wherein the ring-opening polymerization is carried out in the presence of an organic onium compound, an alkali metal hydroxide, or an organic sulfonic acid.
3. 3. The method for producing resin particles according to claim 1, wherein the cyclic polysiloxane compound has a weight average molecular weight of 300 or more and 2,000 or less in terms of polystyrene as measured by gel permeation chromatography (GPC).
4. The method for producing resin particles according to any one of claims 1 to 3, wherein the molecular weight of the chain polysiloxane compound having a polymerizable unsaturated group is 1,000 or more and 3,000 or less in terms of a weight average molecular weight in terms of polystyrene measured by gel permeation chromatography (GPC).
5. 5. The method for producing resin particles according to claim 1, wherein the silane monomer having a polymerizable unsaturated group is a compound represented by the following formula (1): 【Chemistry 1】 [In formula (1), R x represents a group represented by the following formula (2): R a1 , R a3 each independently represents an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, or an acyl group having 2 to 10 carbon atoms, R a2 represents hydrogen, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 10 carbon atoms; 【Chemistry 2】 In formula (2), R a4 represents hydrogen, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 10 carbon atoms; R a5 represents an alkylene group having 1 to 10 carbon atoms, m is 0 or 1; n is 0 or 1; * indicates a bond to Si.
6. A resin particle comprising a chain polysiloxane compound having a structural unit represented by the following formula (3): 【Chemistry 3】 [Formula (3) is —Si(R x ) (R y )O— units are bonded consecutively in a number of o units. o represents an integer of 3 or more; o R x each independently represents an alkyl group having 1 to 10 carbon atoms, An aryl group or a group represented by the following formula (4), x is expressed by the following formula ( 4). o R y each independently represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms. * indicates a bond. 【Chemistry 4】 In formula (4), R b1 represents hydrogen, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 10 carbon atoms; R b2 represents an alkylene group having 1 to 10 carbon atoms, m is 0 or 1; n is 0 or 1; * indicates a bond, ** indicates a bond to Si.]
7. Resin particles as described in claim 6, wherein the content of the structural unit represented by formula (3) having a group represented by formula (4) is 50 mass% or more in 100 mass% of the chain polysiloxane compound.
8. R x The resin particles according to claim 6 or 7, wherein the content of said resin particles is 45% by mass or more and 85% by mass or less.
9. 9. The resin particles according to claim 6, wherein the coefficient of variation of the particle size on a number basis is 10% or less.
10. 10. The resin particles according to claim 6, wherein the resin particles have a breaking strength of 15.00 mN or more, which is a load value at a breaking point of the resin particles in a compression test in which the resin particles are compressed at a load application rate of 2.23 mN / sec.
11. The resin particles according to any one of claims 6 to 10, wherein the compressive deformation recovery rate of the resin particles is 35% or more and 70% or less, as measured by deforming the resin particles between a maximum load of 9.81 mN and a minimum load of 0.10 mN at a load application rate of 1.49 mN / sec.
12. The resin particles according to any one of claims 6 to 11, which have a thermal decomposition temperature of 240°C or higher.
Citation Information
Patent Citations
Production of curable silicone emulsion composition and silicone powder
JP1992072358A
Organic and inorganic composite particle, its production and use
JP2000204119A
Conductive fine particle
JP2014011117A
Spherical gap agent
JP2018163347A